(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article analyze current situation of green financing in Uzbekistan and how functions there are to achieve sustainable economic growth. All of main problems are discussed and given solutions with real cases.